2019
DOI: 10.1007/978-3-030-12512-7
|View full text |Cite
|
Sign up to set email alerts
|

Noise Control of the Beginning and Development Dynamics of Accidents

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…However, the seismic activity in some regions can create problems. The most important and vulnerable elements of rail transport are the moving part of cars and railroad tracks, the insufficient monitoring of the condition of which does not ensure the proper safety of the rolling stock [1][2][3][4][5][6][7][8][9][10]. As the railroad passes through seismically active regions, additional requirements for traffic safety appear.…”
Section: Main Components Of Creating a Railroad Operation Safety Systmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the seismic activity in some regions can create problems. The most important and vulnerable elements of rail transport are the moving part of cars and railroad tracks, the insufficient monitoring of the condition of which does not ensure the proper safety of the rolling stock [1][2][3][4][5][6][7][8][9][10]. As the railroad passes through seismically active regions, additional requirements for traffic safety appear.…”
Section: Main Components Of Creating a Railroad Operation Safety Systmentioning
confidence: 99%
“…This particularly applies to the problems of controlling the onset of the emergency condition of wheels and rails, their vulnerability and derailment conditions. Our analysis of the literature [12][13][14][15][16][17][18][19] devoted to control technologies and control systems taking into account the specific characteristics of railroads of seismically active regions has shown that the use of noise technologies [1] can indeed improve the safety of this mode of transport. To do this, it is reasonable to create a subsystem for noise seismic hazard warning [11], i.e., a subsystem for noise control of the onset of the initiation and dynamics of development of changes in the technical condition of the rolling stock and railroad tracks to incorporate in the existing railroad monitoring systems.…”
Section: Main Components Of Creating a Railroad Operation Safety Systmentioning
confidence: 99%
See 3 more Smart Citations